Adult Learning in Ecotourism: The Current State of Research - Pierre Walter (Adult Education Research Conference, 2009)
This paper reviews research on adult learning in nature, adventure and community-based ecotourism. Aims, learning activities, outcomes and philosophical orientation of each type of ecotourism are analyzed, and areas in need of further research identified.